Ghosts in the house! - Kohara, Kazuno (New York : Roaring Brook Press, 2010)
Tired of living in a haunted house, a young witch captures, washes, and turns her pesky ghosts into curtains, table linens, and bedding
'Square fish'
'A New York Times best illustrated book'--Cover
Keywords: Witches -- Juvenile fiction; Haunted houses -- Juvenile fiction; Ghost stories